An Epichloë festucae homologue of MOB3, a component of the STRIPAK complex, is required for the establishment of a mutualistic symbiotic interaction with Lolium perenne. (14th August 2016) - Green, Kimberly A.; Becker, Yvonne; Fitzsimons, Helen L.; Scott, Barry
Summary: In both Sordaria macrospora and Neurospora crassa, components of the conserved STRIPAK (striatin‐interacting phosphatase and kinase) complex regulate cell–cell fusion, hyphal network development and fruiting body formation. Interestingly, a number of Epichloë festucae genes that are required for hyphal cell–cell fusion, such as noxA, noxR, proA, mpkA and mkkA, are also required for the establishment of a mutualistic symbiotic interaction with Lolium perenne . To determine whether MobC, a homologue of the STRIPAK complex component MOB3 in S. macrospora and N. crassa, is required for E. festucae hyphal fusion and symbiosis, a mobC deletion strain was generated. The Δ mobC mutant showed reduced rates of hyphal cell–cell fusion, formed intrahyphal hyphae and exhibited enhanced conidiation. Plants infected with Δ mobC were severely stunted. Hyphae of Δ mobC showed a proliferative pattern of growth within the leaves of Lolium perenne with increased colonization of the intercellular spaces and vascular bundles. Although hyphae were still able to form expressoria, structures allowing the colonization of the leaf surface, the frequency of formation was significantly reduced. Collectively, these results show that the STRIPAK component MobC is required for the establishment of a mutualistic symbiotic association between E. festucae and L. perenne, and plays an accessory role in the regulation of hyphal cell–cell fusion and expressorium development in E. festucae .